Potensi Dan Prospek Industri Gula Aren Di Indonesia - Putri Intan Suri; Faradina Zevaya; Helen Parkhurst (Journal of Islamic Economics and Finance, 2024)
Palm sugar produced from sugar palm plants is an alternative sugar to granulated (refinery) sugar produced from sugar cane plants. Recently, more and more consumers are switching from granulated sugar to palm sugar. However, because entrepreneurs are still traditional, efforts to meet changing consumer tastes still have many obstacles. This research aims to (1) determine the potential of sugar palm plants as; (2) analyze the prospects for the Indonesian small palm sugar industry in the future. The method for determining the research location was carried out purposively, namely the Republic of Indonesia, which is one of the largest palm sugar producers in the world. This research was carried out from March 2024 to May 2024. This research was carried out using a survey approach and used secondary data, especially BPS publication data. To find out the prospects for palm sugar in Indonesia, it is explained using simple linear regression. Meanwhile, the analysis of plant potential is explained descriptively qualitatively and quantitatively. The research results show that sugar palm cultivation in Indonesia has great potential, especially because sugar palm plants do not require complicated growing requirements. Almost all areas in Indonesia can be planted with palm trees. The availability of land in Indonesia is quite extensive, has hydrological and conservative functions. There is a traditional farming culture in cultivating palm sugar. The results of regression analysis using time series data from 1992 to 2020 show that the development of land area, which is a manifestation of farmers' response to demand for palm sugar, shows an increasing trend. With ß of 1,046.5, it shows that on average every year there is an increase in the area of ​​sugar palm plantations of 1,046.5. Meanwhile, from the production aspect, the results of the regression analysis also show a significant increasing trend with ß of 2,575.4, which shows that from the production aspect there has been a significant increase in production, namely 2,575.4 tonnes each year. Furthermore, it can be concluded that the potential for palm tree development is quite good and the prospects for the palm sugar industry in Indonesia are quite bright.